Pengaruh Tahapan Bioremediasi Terhadap Efektivitas Eliminasi Merkuri (Hg) Di Media Cair - Asri Adelia; Liswara Neneng; Nawan (FKIP Universitas Palangka Raya, 2023)
Gold mining uses mercury for the gold extraction process, where the mercury content in the Kahayan watershed reaches 2.996 - 4.687 µg/l and this value exceeds the standard limit for mercury content in water. Bioremediation is one solution to reduce mercury waste pollution. Mercury bioremediation using microorganisms and adsorbents requires appropriate process steps to be effective in eliminating mercury. This study aims to determine the effect of bioremediation stages on the effectiveness of mercury (Hg) elimination in liquid media and to determine the most effective bioremediation steps for mercury (Hg) elimination in liquid media. This study used an experimental method with a nonfactorial completely randomized design consisting of treatments namely control (K), treatment 1 (T1), treatment 2 (T2), treatment 3 (T3), treatment 4 (T4), with 5 (five) times repetition. Analysis of the results of the bioremediation stages using AAS (Atomic Absorption Spectrophotometry). Data were analyzed using the One-way Anova test, LSD test and effectiveness test. The results showed that the bioremediation stage had a significant effect on the effectiveness of mercury (Hg) elimination in liquid media. The most effective bioremediation stage for mercury (Hg) elimination in liquid media is the T3 stage which starts from Mercury Waste→Microalgae→Bacteria→Red Clay→Activated Charcoal, with an effectiveness value of 89.4% in reducing mercury.